The combined 410nm and infrared light effectively suppresses bacterial survival under realistic conditions - Matthew Stangl; Matthew Stangl; Dinesh Kumar Verma; Dinesh Kumar Verma; Areli Martinez; Yong-Hwan Kim; Yong-Hwan Kim (Frontiers in Cellular and Infection Microbiology)
The demand for establishing an effective but inexpensive method to interfere with the spread of infectious diseases has been higher than ever before, since the recent pandemic. As a follow-up study, we tested a few practically applicable lights with a safe 410nm violet light (V) with infrared (IR, 850nm) under realistic conditions to identify an optimal light for suppressing pathogens. Our results indicate that 410nm violet light is as effective as the previously tested 405nm violet light with infrared (850nm). Therefore, we focused on optimizing combined lights (3V-1IR or 2.33V-1IR) with lower power level that is below 24 Watt. Using the Multi Drug Resistant (MDR) Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) from ATCC, we confirmed that the combined 20W light effectively suppressed the survival of both MDR bacterial strains on a smooth surface at the distance of 25cm, 50cm, 1m or 2m, which mimicked the realistic living spaces. As expected, the effectiveness was inversely proportional to the exposed distance. For example, the light exposure suppressed more than 91-97% of E. coli within 1–2 hours and 96-99% of S. aureus within 2–6 hours at short distances (25 or 50cm), whereas it took 6–8 hours to reach 92-95% of E. coli and 91-99% of S. aureus suppression at 1 or 2m. In the mechanistic studies, we confirmed that the bacterial death was mediated by the enhanced level of Reactive Oxygen Species (ROS), in addition to reduced thickness of biofilm from 410nm and 850nm infrared light. Our results strongly support the possible application of using this combined 410nm with infrared light as an inexpensive and practical solution to reduce the potential pathogens, at least from bacterial origins in a variety of living spaces.